DESIGNING THE IMPROVEMENT OF SPAM UNS WATER DISPENSER SERVICE QUALITY - Natalianto, Yosua; Pujiyanto, Eko; Sutopo, Wahyudi (Jurnal Ilmiah Teknik Industri, 2020)
SPAM (Sistem Pengolahan Air Minum or Drinking Water Treatment System) UNS was established in 2015 to meet the drinking water needs of the UNS academic community by providing 129 dispensers and water tap machines spread across buildings at UNS. A survey conducted by UNS students in 2017 showed that 54 % of students were not sure of the quality of UNS SPAM water. So the service quality questionnaire was distributed to 160 UNS students randomly and it was found that only 3 % of respondents stated that they used SPAM UNS water dispenser very often. Processing results shown the highest gap value is in the reliability dimension, with CTS namely cleanliness and flow of water. From the survey regarding the cleanliness and flow of the water carried out the DPMO value of the process was 332,589 (1, 930 sigma) . Recommendations for improvement are in the form of several SOPs to improve the cleanliness and quality of SPAM UNS water dispenser services.